2012
DOI: 10.1074/jbc.m111.297804
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 Protein Regulates Glycogen Phosphorylase Activation and Controls Interleukin (IL)-2-dependent T Cell Proliferation

Abstract: Background: Rac1 has a relevant role in signal transduction pathways in T lymphocytes. Results: Rac1 GTPase associates with glycogen phosphorylase and modulates its enzymatic activity to trigger T cell proliferation. Conclusion: This study reveals a new role for Rac1 GTPase in cellular physiology, coordinating metabolism and proliferation. Significance: This new Rac1/PYGM pathway might be essential for an appropriate immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 71 publications
2
43
0
Order By: Relevance
“…Moreover, Rac 1 has also been found to participate in IL-2-induced actin cytoskeleton rearrangement in a murine T cell line (12). More recently, our group reported that Rac 1 binds and activates the glycogen phosphorylase muscle isoform (PYGM) 3 and thus established a novel metabolic pathway that participates actively in IL-2-stimulated cell proliferation in human T cells (13). Signals emanating from a large variety of membrane receptors: growth factor receptors (14,15), G protein-coupled receptors (16,17), and tyrosine kinases-linked receptors such as TCR (5,18), BCR (19,20), and IL2-R (13), actively regulate Rho GTPase effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Rac 1 has also been found to participate in IL-2-induced actin cytoskeleton rearrangement in a murine T cell line (12). More recently, our group reported that Rac 1 binds and activates the glycogen phosphorylase muscle isoform (PYGM) 3 and thus established a novel metabolic pathway that participates actively in IL-2-stimulated cell proliferation in human T cells (13). Signals emanating from a large variety of membrane receptors: growth factor receptors (14,15), G protein-coupled receptors (16,17), and tyrosine kinases-linked receptors such as TCR (5,18), BCR (19,20), and IL2-R (13), actively regulate Rho GTPase effects.…”
mentioning
confidence: 99%
“…For transient transfections, cells were cultured in complete RPMI 1640 medium in the absence of IL-2 for 24 h. Thereafter, cells were washed, resuspended in 200 l of serum-free medium, and placed in an electroporation cuvette (0.4 mm, Sigma) containing 10 -20 g of different plasmids, or 15 ng of esiRNAs. Electroporation was carried out in a Gene Pulser Xcell Electroporator (Bio-Rad) at 260 V and 950 microfarads (13). The cuvette content was collected into 10 ml of complete RPMI 1640 medium and cultured in the absence of IL-2 for an additional 24 h.…”
mentioning
confidence: 99%
“…In this way, they control a wide variety of cellular processes among which are the actin cytoskeleton reorganization, the formation of integrin complexes, cell adhesion, gene transcription, cell cycle progression, and cell proliferation [4,5,[32][33][34]. In fact, the control of CDKs by the activation of the growth factor-dependent Ras/MAP kinase pathway [35] , were maintained in the serum-free medium for 24 h and stained with PKH26.…”
Section: Discussionmentioning
confidence: 99%
“…This molecular structure and its potential to establish intermolecular interactions result in a complex and flexible platform for both recognition and processing information as well as the transduction of signals to the cell cytosol and the nucleus. B lymphocytes may be maintained in a quiescent state and stimulation of BCR leads to potent activation of signalling molecules, such as the small GTPases of the Ras superfamily [2][3][4][5] mediating the activation of intracellular signalling cascades [2][3][4][5][6][7][8][9]. Briefly, BCR stimulates the activity of both the Syk [10,11] and the Src family of protein tyrosine kinases [12] leading to the activation of the B cell signalosome, which includes the adapter protein BLNK (B cell linker-protein), Bruton's tyrosine kinase (BTK) and phospholipase Cc2 (PLCc2) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…There were also a number of studies by other groups using Taqman based gene expression analysis with RNA extracted with TRIzol reagent [156][157][158][159][160][161][162] …”
Section: Taqman Gene Expression Assay Using Rna Extracted With Trizolmentioning
confidence: 99%